The interactive technologies of study Ukrainian as a foreign language: structural analysis - Shleneva, M. G. (Харківський національний автомобільно-дорожній університет, 2017)
At the present stage of integration process Ukrainian higher education institutions go through the difficult period of reforming. According to the new "Education law", modern higher education institutions will have the system reconstructions of educational process and transition to the modernized educational approach both for Ukrainian and foreign students. Thus, the idea of practical orientation of Ukrainian as a foreign language is approved in activity of language departments. First of all it is necessary to teach foreign students to read, to write, to speak Ukrainian and also to work independently with textbook. The basis issue of all educational transformations should be understanding of foreign student’s capacities and forecasting of personality development requirements in the conditions of adaptation. That’s why on a practical classes of Ukrainian as a foreign language the teacher of higher education institution is faced by a difficult task: to teach students to listen, to perceive, to remember a studying material, to develop the creative potential. The developing purposes have to be defined according to a concrete studying material and provide students with knowledge, practical skills, requirements to perform educational tasks creatively and qualitatively.
Keywords: foreign students; Ukrainian language; interactive technologies; foreign language